Prevalence of Nosocomial Infections in Surgical Ward at Butare University Teaching Hospital - Munyembaraga, Valens; Claude Bayingana,; Christian Ngarambe, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
BACKGROUND: Health care associated infections which include Nosocomial infection remain a foremost public health burden worldwide. Bacterial resistance is an increasing therapeutic challenge which is associated with nosocomial infections. Thus, the main objective of this study was to identify the prevalence of surgical site infections.  METHODS: A cross sectional quantitative study was conducted in surgery of CHUB. Patients undergone operation were recruited from January 2017 until we reach 221 patients. Clinicians followed patients on a daily basis until discharge. In case of clinical signs and symptoms of surgical site, biological specimen were collected and processed in laboratory for bacterial isolation. RESULTS: Out of 221 patients operated in hospital, 6.8% were confirmed of bacterial nosocomial infections. The rate of surgical site infections is associated with the theatre, class of wound, where clean and clean/contaminated operations was 3.13% and 8.00% respectively which increase to 15.79% and 29.41% for contaminated and dirty/infected wound respectively. A total of 19 samples collected, Staphylococcus aureus was the identified in 6 samples accounting 37.50% and then Coagulase Negative Staphylococcus species at 25.00%. CONCLUSIONS: Drug resistance of isolates to antimicrobials is an alarming risk of nosocomial infections considering the empirical prophylactic and treatment in places. adherence of aseptic surgical procedures and proper management of wounds is demanding in the process to counter the infection.